Cyber Ethics dan Kecerdasan Buatan dalam Digitalisasi Peradilan Agama di Indonesia Perspektif Maqashid Syariah - Putri Humaira Djufri; Icksan Asry Fabanjo (Al-Kindi, 2026)
The rapid digital transformation of Indonesia's judiciary, including the Religious Courts (Pengadilan Agama), raises urgent ethical and legal questions once artificial intelligence (AI) is introduced into the settlement of Islamic family law disputes. This article examines how cyber ethics, understood through the lens of maqasid al-shari'ah, the five higher objectives of Islamic law, can function as a normative and pedagogical bridge where positive law has not yet caught up with technological change. Using a normative-juridical method with statutory, conceptual, and case-illustration approaches, the discussion maps each maqasid (protection of religion, life, intellect, lineage, and property) against concrete AI risks, covers the regulatory infrastructure of e-Court and e-Litigation, the opportunities and algorithmic risks of AI in adjudicating divorce, custody (hadhanah), and inheritance (waris) cases, the protection of sensitive family data, the boundaries of judicial discretion (diskresi hakim), and the correlation between maqasid-based curriculum reform in Islamic legal education and the cultivation of AI literacy among future judges, advocates, and litigants. The analysis finds that while digitalization improves efficiency and access to justice, unchecked reliance on AI risks algorithmic bias, erosion of judicial independence, and exposure of highly sensitive family data, and that these risks can only be sustainably mitigated through maqasid-based education reform alongside regulation. The article recommends that the Supreme Court and Religious Courts adopt risk-based, sharia-compatible AI governance guidelines, and that Islamic legal education institutions integrate maqasid-based cyber ethics literacy into their curricula, with substantive justice as the ultimate objective of Islamic family adjudication.